Shared Leadership Improves Team Novelty: The Mechanism and Its Boundary Condition - Sun, Xiaomin; Jie, Yuan; Wang, Yilu; Xue, Gang; Liu, Yan (Frontiers in Psychology, 2016)
Previous research has revealed the significant impact of shared leadership on team creativity, yet the mechanism underlying this relationship has rarely been investigated. The current research examined how shared leadership influenced team creativity (novelty and usefulness) across 3 studies using both long-term project teams and temporal task teams in the laboratory. The results showed that shared leadership enhanced the novelty dimension of team creativity by improving constructive controversy. Furthermore, team goal orientation moderated this effect. The indirect effect of constructive controversy holds for teams with learning goal orientation but not for those with performance goal orientation. Such patterns were not found in the usefulness dimension of team creativity.